Prevalence of primary HIV-1 drug resistance among antiretroviral-naïve individuals in Togo in 2023: a national study - Ouro-Medeli, Alassane; Togan, Roméo M.; Serrano, Laetitia; Butel, Christelle; Atoun, Rogatien; Youa, Frederic; Ali-Edje, Komlan; Douffan, Messanh; Ehlan, Phyllis; Tegueni, Kokou; Amenti, Romaric; Konou, Abla Ahouefa; et al. (Frontiers in Public Health, 2025)
Monitoring pre-treatment drug resistance is a priority to assess the emergence of HIV resistance to antiretrovirals, especially in countries where the transition from dolutegravir-based regimens is already effective on a large scale. The aim of this study was to estimate the prevalence of resistance mutations to different classes of antiretrovirals (ARVs) in HIV-1-naïve persons in Togo in 2023. A cross-sectional study was conducted in 30 HIV care centers for people living with HIV in Togo between March and August 2023. Persons newly diagnosed with HIV-1, aged 18 and over and naïve to any ART with a viral load ≥ 6500.00 copies/ml were included for genotypic resistance testing for protease (PR), reverse transcriptase (RT) and integrase (IN) genes using Next-generation sequencing. Mutations were interpreted using the updated Stanford HIVDB and ANRS algorithms after genotypic testing for protease, reverse transcriptase and integrase resistance. Among 376 enrolled people living with HIV (PLHIV), resistance analyses were carried out on 321 samples. The median age was 39 years, Interquartile range (IQR) [30-47] and 64.9% were women. No resistance mutations to dolutegravir (DTG) were detected. However, accessory mutations (genetic changes that do not confer significant resistance by themselves) as E157Q/E157EQ (43/57) and T97A/T97TA (14/57) associated with resistance against first-generation integrase inhibitors (INIs) as raltegravir, elvitegravir were found in 17.2% of samples. No major mutations (genetic changes that, on their own, confer high-level resistance of the virus to one or more antiretroviral drugs) were observed in the protease gene. The mutations as T215TS and K70KE (detected as a mixture) associated with possible resistance were detected in 0.6% (2/316) for NRTIs and 6.3% (20/316) for NNRTIs. The most frequent NNRTI mutations were K103N (4.4%) and G190A (1.3%). The dominant subtypes were CRF02_AG (64.8%) and CRF06_cpx (12.8%). These results support the continued use of dolutegravir-based regimens in Togo and call for continued monitoring of primary resistance to maintain the effectiveness of therapeutic strategies in Togo.